Atteintes Oculaires Au Cours Du Syndrome De Wolfram Ã€ Propos De Deux Cas Et Revue De La LittÃ©rature - H.Y, Abba Kaka; N., Guirou; C.R., Berete; A., Amza; M., Daou (European Scientific Journal, ESJ, 2017)
Introduction: Wolfram syndrome is an autosomal recessive neurodegenerative disorder. Diabetes mellitus and juvenile bilateral optic atrophy are its major signs. It is recognized that this association, which started in childhood or during adolescence, is sufficient to diagnose Wolfram syndrome. Optic atrophy occurs in 98% to 100% of cases with an average age of onset of 11 years. We reported a study of two confirmed cases referred by the internal medicine department. Observations: Case 1: A 23- year-old woman, deaf and dumb by birth, went through a diabetic ketosis test. Ophthalmologic examination showed reduced visual acuity in the fingers at 5 meters P2 in both eyes. Also, the fundus of the eye showed bilateral atrophic papillary palpation with no signs of retinopathy. She had deafness of deep perception and hypogonadotropic hypogonadism. Deafness, diabetes, optic atrophy, and hypogonadism led to the diagnosis. Case 2: A 21-year-old man born from a first-degree consanguineous marriage serves as a supplement to the management of diabetes. The visual acuity was at counting fingers at 1m to the right eye and sees the hand move to 0.5 m to the left eye. On examination at the slit lamp, it had a bilateral dense cataract. After phacoexeresis, the base revealed bilateral optic atrophy. Ultrasound of the urinary tree showed hypotonia of the renal cavities and a neurogenic bladder. Also, audiometry showed mild sensory deafness. The diagnosis of Wolfram syndrome was made in front of the tetrad: diabetes, optic atrophy, deafness, and urinary signs. Discussion: Wolfram syndrome may be familial or sporadic. The gene however is located on the short arm of chromosome 4. Optic atrophy is secondary to the involvement of pre-genetic fibers, and it is characterized initially by temporal palpation of the papilla. The evolution towards diffuse whitish discoloration occurs in a few months or years with the gradual establishment of a blindness around the age of 17 to 30 years. Conclusion: Wolfram syndrome is a clinical entity characterized by clinical and genetic polymorphism. This diagnosis should be considered in the presence of any type I diabetes associated with optic atrophy in children